Information-Theoretic Quantification of Dedifferentiation in the Aging of Motor and Executive Functions - Chang, Erik Chihhung (Frontiers in Aging Neuroscience, 2021)
A central account of cognitive aging is the dedifferentiation among functions due to reduced processing resources. Previous reports contrasting trends of aging across cognitive domains mostly relied on transformed scores of heterogeneous measures. By quantifying the computational load with information entropy in tasks probing motor and executive functions, respectively, the current study uncovered interaction among age, task, and load as well as associations among the parametric estimates of these factors at the individual level. Specifically, the linear functions between computational load and performance time differed significantly between motor and executive tasks in the young but not the elderly, and showed stronger associations for parameters within and between tasks in the elderly than in the young. These findings are in line with the dedifferentiation hypothesis of cognitive aging, and provide a more principled approach in contrasting trends of cognitive aging across different domains from the information theoretic perspective.